Population impact to bald eagles by ingested lead in New York State, 1990–2018 - Brenda J. Hanley; Cara E. Them; Kevin P. Hynes; Patrick J. Connelly; Elizabeth M. Bunting; Krysten L. Schuler (Wildlife Society Bulletin, 2023)
Abstract While the recent population recovery of bald eagles (Haliaeetus leucocephalus) in New York State, USA, is a conservation success, evidence from necropsies suggest that ingested lead (Pb) from ammunition fragments is causing morbidity and mortality to wild eagles. Wildlife managers and officials at the New York State Department of Environmental Conservation would benefit from analysis of their necropsy data to understand how documented morbidities or mortalities impact dynamics of the remaining wild eagle population. We integrated necropsy data on bald eagles in New York State collected between 1990 and 2018 by the New York State Department of Environmental Conservation into a matrix population model. We compared annual survival of hatchling, non‐breeding, and breeding eagles under factual (Pb) and counter factual (Pb‐reduced or Pb‐free) scenarios. We found no evidence that Pb altered annual survival of hatchlings. Lead was associated with a reduction in the annual survival of non‐breeders by 0–0.056 (females) and 0.052–0.057 (males), and a reduction in the annual survival of breeders by 0.051–0.057 (females) and 0–0.032 (males). Lead was associated with a reduction in the long‐term growth rate (λ) by 0.009–0.036 (females) and 0.023–0.035 (males). Due to altered dynamics over the prior 3 decades, abundances of eagles in the most recent year of the study (2018) differed between Pb and non‐Pb systems; Pb was associated with a reduction in the number of total females by 15–610 birds, but an increase in the number of total males by 43–95 birds. The interactive software depicting these and other results is available for public use. Our study provides state‐specific evidence of the population‐scale impact of Pb ammunition on bald eagles and may be helpful to wildlife officials in the creation of educational materials or regulatory measures in habitats that support free‐ranging bald eagles.